CONSTITUTIONALIZATION OF RELIGION IN REVIEW OF MAQÂSHID SHARÎ‘AH: Statutory Study of Shariaism in the City of Langsa, Aceh - Harahap, Ikhwanuddin; Nasution, Adelina (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2023)
Abstract: This article aims to analyze two regulations Langsa City Qanun Number 3 of 2016 concerning the implementation of entertainment in Langsa City and Langsa Mayor’s Regulation Number 40 of 2020 concerning Guidelines for Granting Permits to Organize Entertainment in Langsa City based on a sharia maqâshid review. The study of the two regulations uses Paul Ricoeur’s hermeneutics with the technique of constitutional distinction, appropriation into social contexts, and interpretation in the perspective of maqâshid al-sharî‘ah by al-Syatibi. The research findings show that there are still many points of existing regulations that are not in accordance with several dimensions of maqâshid al-sharî‘ah. The infiltration of sacred religion into a technical system that is profane and its interpretation by certain groups is not in accordance with maqâshid al-sharî‘ah in the dimension of religious benefit. The regulation of Shari’a causes religion to regulate private spheres such as religion and the way of dress, contrary to the dimension of maintaining common sense. Keywords: shariatisme, Aceh, entertainment area, regulation, maqâshid al-sharî‘ah